A viral vector model for circuit-specific synucleinopathy - Lantheaume, Alexia (2023)
In Parkinson's disease (PD), pathomechanisms such as aberrant network dysfunctions can be elucidated by conducting multiscale explorations in animal models. However, the lack of specificity in the existing models limits a restricted targeting of individual network elements and characterization of PD as a “circuitopathy”. We therefore developed a cell-type specific viral vector (AAV2/9-CreON-A53T-αSyn) mouse model that allows to induce synucleinopathy within individual circuit elements in vivo. When specifically targeted to dopaminergic (DA) neurons of the substantia nigra pars compacta (SNc), our approach recapitulates the main hallmarks of the disease, namely Lewy-body-like aggregation, progressive cellular and nigrostriatal projections loss, together with locomotor impairment. Our strategy is supported by new state-of-the-art analytical approaches for cell quantification and behavior characterization. Altogether, we provide a novel model of synucleinopathy, which offers new opportunities to study the contribution of individual network elements to disease pathomechanisms.